Pengaruh Manajemen Konflik Terhadap Kinerja Guru di Madrasah Aliyah Negeri (MAN) Kabupaten Labuhanbatu Selatan - Aulia, Destya; Aziza, Riska; Nasution, Inom; Noperiyanti, Yola; Hajar, Siti; Salsabila, Adliya; Lubis, Selfie Purnama; Matondang, Maqbul (Ikatan Da'i Indonesia, 2024)
The study aims to identify and analyze the impact of Conflict Management on the performance of Madrasah Aliyah State Teacher (MAN) in Labuhanbatu South district. The population in this study is a permanent teacher and a non-permanent teacher Madrasah Aliyah State District of Labuhanbatu South. which has a total of 94 people. The research methods used are validity and realism testing of research instruments, descriptive analysis methods, classical assumption tests, double linear regression analysis, t-tests, f tests and determination coefficients. (R2). The hypothesis test results with partial test (test t) show that the variables used are vertical conflict and horizontal conflict have a significant impact on the performance of Madrasah Aliyah State teacher in Labuhanbatu South district.